CO2-looping in pyrolysis of horse manure using CaCO3. (10th February 2018) - Jeong, Kwang-Hwa; Choi, Dong-Ho; Lee, Dong-Jun; Kim, Jung Kon; Kim, Hana; Ok, Yong Sik; Kwon, Eilhann E.
Abstract: This study laid a great emphasis on the mechanistic understanding of CO2 in pyrolysis of horse manure to establish a virtuous cycle for carbon in the thermo-chemical process. To this end, CaCO3 was used as a possible candidate for the CO2 resource to impart synergistic environmental benefits. This study also proved the genuine roles of CO2 in pyrolysis of horse manure. CO2 could be a driving force to shift carbon distribution from pyrolytic oil to pyrolytic gas ( i.e., the enhanced generation of CO), which provides a new means for modifying the composition of syngas as well as pyrolytic oil. Shifting carbon distribution from pyrolytic oil to pyrolytic gas could be explained through two genuine roles of CO2 in pyrolysis of horse manure. For instance, CO2 led to the enhanced thermal cracking of volatile matters evolved from the thermal degradation and the direct reaction between CO2 and volatile matters to form CO, which lead to the enhanced generation of syngas and the reduction of tar formation. These identified genuine roles of CO2 were initiated temperatures higher than 500 °C, when temperature could be decreased down to 450 °C in the presence of CaCO3 due to the catalytic effects arising from CaCO3 . Thus, all experimental findings will be directly applicable to gasification since pyrolysis is an intermediate step in the gasification process. Moreover, the high content of CaO in biochar can be reused in the diverse environmental applications. However, the optimal conditions, especially for optimal CaCO3 loading, should be established through further study on the subject.